Reconstructing Traditional Knowledge Protection through Collective Rights - Abd Thalib; Abu Bakar Munir; Nur Aisyah Thalib; Virender Kumar Ahuja (Contrarius Indonesia, 2026)
Despite the growing international recognition of traditional knowledge (TK) as a strategic asset for biodiversity conservation, innovation, and sustainable development, limited scholarship has examined how fragmented legal regimes and the absence of collective rights recognition undermine its effective protection. This research aims to analyze the weaknesses of Indonesia’s current legal framework and formulate a more comprehensive protection model based on collective rights and sustainable development principles. This research employs a normative juridical method using statutory, conceptual, and comparative approaches. The analysis focuses on Indonesian regulations and compares them with the protection systems implemented in India and Malaysia. The findings demonstrate that Indonesia's legal framework remains fragmented across sectoral regulations, resulting in overlapping institutional authority, limited legal recognition of indigenous communities as collective rights holders, and the absence of binding mechanisms for Free, Prior and Informed Consent (FPIC) and Access and Benefit-Sharing (ABS). In contrast, India strengthens defensive protection through the Traditional Knowledge Digital Library (TKDL) and anti-biopiracy mechanisms, whereas Malaysia provides a more operational ABS framework supported by dedicated biodiversity legislation. However, both jurisdictions continue to rely predominantly on state-centered governance and provide only limited indigenous autonomy. Based on these findings, this research proposes a sui generis legal framework that integrates collective ownership, FPIC, ABS, community-based governance, customary dispute resolution, and collective legal standing into a unified protection regime. The proposed model contributes to strengthening legal certainty, enhancing indigenous participation, harmonizing fragmented regulations, and promoting sustainable management of traditional knowledge in Indonesia.